The book of gutsy women - Clinton, Hillary Rodham (Simon & Schuster, 2019)
Hillary Rodham Clinton and her daughter, Chelsea, share the stories of the gutsy women who have inspired them -- women with the courage to stand up to the status quo, ask hard questions, and get the job done. Ensuring the rights and opportunities of women and girls remains a big piece of the unfinished business of the twenty-first century. While there's a lot of work to do, we know that throughout history and around the globe women have overcome the toughest resistance imaginable to win victories that have made progress possible for all of us. That is the achievement of each of the women in this book. So how did they do it? The answers are as unique as the women themselves. Civil rights activist Dorothy Height, LGBTQ trailblazer Edie Windsor, and swimmer Diana Nyad kept pushing forward, no matter what. Writers like Rachel Carson and Chimamanda Ngozi Adichie named something no one had dared talk about before. Historian Mary Beard used wit to open doors that were once closed, and Wangari Maathai, who sparked a movement to plant trees, understood the power of role modeling. Harriet Tubman and Malala Yousafzai looked fear in the face and persevered. Nearly every single one of these women was fiercely optimistic -- they had faith that their actions could make a difference. And they were right. To us, they are all gutsy women -- leaders with the courage to stand up to the status quo, ask hard questions, and get the job done. So in the moments when the long haul seems awfully long, we hope you will draw strength from these stories. We do. Because if history shows one thing, it's that the world needs gutsy women.